SINCERITY IN RELIGIOUS SPEECH - Mirzakamolova Sadokatxon Sayidaxmadovna (Scholar Express Journal, 2023)
This article explores the concept of sincerity in religious speech. It examines the importance of sincerity in religious communication and the methods that can be used to convey sincerity in speech. The article also discusses the results of studies on the relationship between sincerity and the effectiveness of religious communication, and provides suggestions for promoting sincerity in religious speech.
Keywords: sincerity; religious speech; communication